Analisis Kekuatan Struktur Penopang Overhead Crane Kapasitas 2 x 20 Ton - Supryanto, Joni; Sukarnoto, Tono; Soeharsono, Soeharsono (Universitas Trisakti, 2019)
This research investigated the design of the overhead crane supports with capacity of 2 x 20 ton. The crane design was modeled using both solids and surfaces, and the analysis was performed with finite element method. The results from the analysis verified the stress level, deflection level from crane column and runway beam, and the critical load of buckling for crane column to prevent the structure failure. The stress level result was compared to the material yield strength to find out whether or not the design is safe. It is concluded that the stresses arising from the rail beam and column are still within the permissible limits so that the design is safe to use.